Antenatal Appointment Invitations: Getting the Message Across. (2nd October 2020) - Osiadacz, Katarzyna; Currie, Barbara
Abstract : In line with the Universal Health Visiting Pathway in Scotland, health visitors offer all expectant mothers a pre-birth visit in an antenatal letter. The town of Kirkcaldy on the east coast of Scotland has a diverse community and faced low uptake of antenatal visits (50%), with antenatal letters only sent in the English language. This article outlines how the team undertook to improve uptake of antenatal visits and understanding of the health visiting service through accessible language in the antenatal letter. Providing the letter in the expectant mother's native language improved uptake of the antenatal contact and increased understanding of the health visitor role. It is concluded that it is important to be inclusive and to provide equality of service for multicultural communities, in order to improve outcomes for all children.